Usability Analysis of the Ikan Musi Mobile Application Using the System Usability Scale (SUS) - Lusi Safitri; Catur Eri Gunawan; Muhammad Son Muarie (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The Ikan Musi Mobile Application is an application developed by the Fisheries Department of the Musi Banyuasin Regency Government in 2021. This application is an Android/web-based platform aimed at improving the information system and facilitating information access for the public. This study was conducted to analyze the usability level of the Ikan Musi Mobile Application using the System Usability Scale (SUS). The research method used by the author is a quantitative approach. The theoretical foundation serves as a guide to ensure the research focus aligns with the real conditions in the field. Data collection in this study was carried out by distributing questionnaires to respondents. All questionnaires collected during the research process were processed and classified using Microsoft Excel 2013 spreadsheet software, then analyzed using the SUS method. Based on the research conducted with 15 respondents, usability testing of the Ikan Musi Mobile application using the System Usability Scale (SUS) method yielded an average score of 85.5, indicating that the application is considered to be highly usable.